Estimating willingness to pay for a threatened species within a threatened ecosystem. Issue 8 (3rd August 2017) - Decker, Kevin A.; Watson, Philip
Abstract : This study conducts a choice experiment to determine the willingness to pay for Palouse Prairie conservation. The giant Palouse earthworm ( Driloleirus americanus ), a rare species endemic to the Palouse region, is included as an attribute of conservation and serves as a method for determining the willingness to pay for protecting the species. This method evaluates the value of the earthworm as an attribute of an overall willingness to pay for threatened ecosystem preservation rather than a direct willingness to pay for protecting the species. This method is expected to yield a more accurate measure of willingness to pay for rare species. The annual willingness to pay per household for the giant Palouse earthworm is 20.45 based on the conditional logit model and 19.30 based on the mixed logit model. Ranking and relative importance are included as methods for representing a non-monetary value and importance of the giant Palouse earthworm.